David Watson 1949-2015: A life in higher education (UCL Press, 2016)
A seminar to reflect on David Watson's many and varied contributions to higher education policy, scholarship, and practice was held at the UCL Institute of Education, University College London on 12 November 2015. The principal speakers were Paul Ashwin, Bahram Bekhradnia, Mike Boxall, Rob Cuthbert, Brenda Gourley, Alison Kennell, and Peter Scott. This paper offers a summary of their talks and also attempts to reflect contributions from other participants. Given the extent of editorial licence needed to bring these varied contributions together in what I hope is a reasonably concise and consistent form, responsibility for what follows must rest with me.